OP65 Relationship between gastrointestinal infections and ethnicity in the UK: a systematic review of quantitative studies. (26th August 2022) - Zahair, Iram; Wickham, Sophie; Rose, Tanith; Oyebode, Oyinlola; Clayton, Stephen; Hawker, Jeremy; Whitehead, Margaret; Ghosh, Iman; Barr, Benjamin
Abstract : Background: Inequalities in gastrointestinal infections exert a significant public health burden on UK healthcare services and the community. Studies on gastrointestinal infections have suggested conflicting findings on where ethnic inequalities are likely to persist. This systematic review was warranted to assess, systematise and interpret the conflicting evidence. The aims were to identify studies that ascertain differences in the incidence and prevalence of gastrointestinal infections within and between UK ethnic groups and explore possible explanations for heterogeneity observed within the literature. Methods: The protocol was registered (PROSPERO CRD 42021240714). Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance, a systematic review methodology was used. Medline, Web of Science, CINAHL Plus and grey literature using Google Scholar were searched from 1980 to 2020 for studies reporting an association between ethnicity and gastrointestinal infections in a representative UK population sample. Studies describing quantitative findings using an observational study design and drawing comparisons between two or more ethnic groups were considered for inclusion. Two reviewers independently screened the articles exported into EndNote and later Rayyan and conducted quality appraisals; data extraction was undertaken by one reviewer and verified by two reviewers using standardised data extraction forms created in Word. The Liverpool Quality Assessment Tools were used to evaluate potential sources of bias. A narrative synthesis was undertaken to synthesise the study findings. Harvest plots supported the textual synthesis. Results: The reviewers identified 8134 studies; 13 met the inclusion criteria. The studies were mainly cross-sectional by design (n=6), followed by cohort (n=4) and ecological (n=2), while one used both cross-sectional and cohort study designs. Many were conducted in the mid-2000s. 12 out of 13 studies found a consistent difference in the prevalence of gastrointestinal infections between different ethnic groups. UK ethnic minorities, predominantly children of Pakistani ethnic origin, have an increased risk of infection. Studies reported that age and sex confounded the relationship between ethnicity and gastrointestinal infections, while the place of birth, socioeconomic status, and geographical location mediated this association. Conclusion: This systematic review elucidates the lack of comprehensive UK quantitative evidence examining the association between ethnicity and gastrointestinal infections. Insights into gastrointestinal infections and ethnicity's association can help address policy actions to mitigate the inequalities identified within and between UK ethnic groups.